Bio-Duck Activity in the Perth Canyon. An Automatic Detection Algorithm. - McCauley, Robert; Matthews, Dave; Macleod, Rodney (Springer Nature, 2004)
Recently analysed data from Curtin University has revealed a significant amount of “bio-duck” activity in the Perth Canyon during December 2002. The name “bio-duck” originates from sonar operators on board the old Oberon class submarines who thought that the sound resembled that of a duck. Surprisingly this is not the case for the Curtin data. The difference however may be due to onboard audio processing prior to the operators hearing the sound that was absent in the Curtin data. It should also be noted that for both data sets the origin of the sound is unknown. For the recent data there exists two distinct types of call. One long period (T~3.1 sec) and one short period (T~1.6 sec) covering the frequency range 60 Hz < f < 1000 Hz. This could have major implications on the operations of some of the sonar on-board the Collins class submarines. Consequently an algorithm was written to automatically detect the presence of bio-duck. In order to eliminate the effect of amplitude variations between data files a signal-time ratio method was used for a third octave band centred around 125 Hz. The reliability of this algorithm was estimated by comparing it’s output with that of the manual analysis of 2240 data files (23 days). It was found to have a 93% success rate in detecting the bio-duck. This will allow quick analyse of large amounts of data to investigate annual variations and also give a method for automatic detection on board the submarines. The results will be discussed.